Correlation of Length of Fever before Hospital Admission, Hematocrit, Platelet Count, and Leukocytes with Length of Hospitalization Dengue Virus Infection Patients in Children - Pambudi, Nasrurrofiq Risvana Bayu; Puspitasari, Metana; Jatmiko, Safari Wahyu; Aisyah, Riandini; Alfajri, Asri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: To analyze the relationship between fever duration before admission, hematocrit, platelet count, and leukocyte count with length of hospital stay in pediatric patients with dengue infection. Methodology: This observational study with cross-sectional design was conducted at PKU Muhammadiyah Sampangan Hospital, Surakarta, using secondary data from medical records. Forty pediatric patients were selected through consecutive non-probability sampling technique. Statistical analysis was performed with Spearman correlation test using statistical applications. Results: There was a significant association between fever duration before admission and length of hospitalization (r = -0.407, p = 0.009). However, there was no significant association between hematocrit (r = 0.136, p = 0.403), platelet count (r = 0.101, p = 0.536), or leukocyte count (r = 0.111, p = 0.496) with length of hospitalization. Applications/Originality/Value: This study highlights the importance of early detection and intervention in managing pediatric dengue cases. The significant correlation found between fever duration prior to admission and length of stay underscores the need for prompt treatment to minimize hospital stay due to associated inflammation in the body. In contrast, the lack of significant associations between hematocrit, platelet count, leukocyte level and duration of hospitalization highlights the complexity of factors influencing outcomes and the need to explore other prognostic markers. This study conducted in an endemic region of Indonesia contributes to understanding the management of dengue virus infection and underscores the importance of a comprehensive multifactorial approach to improve patient care strategies.